Effect of pore pressure distribution on fracture behavior of sandstone in nitrogen fracturing. Issue 5 (September 2017) - Hou, Peng; Gao, Feng; Gao, Yanan; Yang, Yugui; Cai, Chengzheng
To investigate the effect of pore pressure distribution on fracture behavior of rock in gas fracturing, nitrogen fracturing experiments on the sandstone are performed under different gas filtration conditions. Results indicate that the breakdown pressure of the sandstone reduces with the decreasing amount of gas filtration. In no gas filtration case, the breakdown pressure value of the sample decreases by 69.98 and 45.6% in comparison to no gas invasion case and gas filtration case, respectively. The failure pattern of the sandstone sample is determined by borehole pressure and pore pressure, and it is mainly controlled by borehole pressure at high injection rate and controlled by pore pressure at low injection rate. In addition, pore pressure can promote microcracks initiation and high pore pressure distribution contributes to generating complex multifractures network. Furthermore, in order to popularize the experimental results to the field application, a method of special graded particles is proposed to temporarily plug induced and natural fractures during fracturing process and then prop these fractures after fracturing. The method is expected to improve fracturing efficiency and increase production of oil and gas in practical application.